Study over the harmonic effects in electrical distribution networks - Ioana, Gabriel; Cazacu, Emil; Petrescu, Lucian; Stănculescu, Marilena (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
This paper analyses the implementation of modern remedial measures to current, and voltage distortion problems generated by power nonlinear industrial loads. For these types of heavily polluted consumers, traditional solutions such as passive or hybrid filters are not suited. Consequently, the active harmonic filters (AHF) are the only pieces of equipment to be considered. Their proper selection is attained only after performing an adequate power quality audit of the main electric parameters at the main low voltage switchboards. The paper presents an AHFbased solution for nonlinear industrial load which reduces the current and voltage harmonics. The solution is validated by harmonics measurements before and after AHF installation.